Sole Epidural Anaesthesia for Caesarean Section in a Patient with Multiple Sclerosis: A case Report and Literature Review - neupane, Biplov; Baral, Dilip; Parajuli , Bashudev (Medical Journal of Shree Birendra Hospital, 2023)
Neuraxial blocks in patients with multiple sclerosis has been controversial, because the effect of local anaesthetic drugs on the course of the disease is unclear. We report an obstetric patient with multiple sclerosis whose Caesarian section was performed successfully under sole epidural anesthesia and postoperative pain control was managed using epidural morphine. There were no exacerbations of neurologic symptoms and no relapse of disease at one month follow-up. We suggest that the choice of anaesthetic technique for patients with multiple sclerosis should be determined after evaluation of the course of the disease and informed consent.